Community Empowerment Through Non Formal Education - Fahmi, Muhammad (Devotion : Journal of Research and Community Service, 2019)
mpowerment means encouragement ormotivation, guidance, or assistance in increasing theability of individuals or communities to be able to beindependent. This effort is a stage of the empowermentprocess in changing behavior, changing old habits to newgood behaviors. In the Pandemic era like the one that hittoday, the condition of formal education activities wasreally empty. Conditions and government policies thatforce people to limit activities including formal education.In the era of the Covid 19 Pandemic, implementing ororganizing education is something that is difficult to do.The government policy regarding the existence ofrestrictions on activities (social distancing) resulted in afreeze in the activities of the formal education world. Inthis context, the importance of non-formal education isto meet the educational needs of children in thecommunity. The existence of non-formal education willgreatly help the community in terms of limited activitiesin social life. Cempaka Village has non-formal educationactivities which are engaged in the education of readingand writing al-Qur'an starting from Juz Ammah to beingproficient in reading al-Qur'an. This non-formaleducation accepts students from the age of 6 to 17 years.